Argumentative Analysis of the Constitutional Court Judgment in PUCP Case - Morales Luna, Félix (2010)
The purpose of this article is to contribute to the discussion of the legal arguments contained in the sentence issued by the Constitutional Court. The topic discussed was the constitutional protection filed by the Pontificia Universidad Católica del Peru against the judgment of the Eighth Civil Chamber of the Superior Court of Justice of Lima, which was declared unfounded. The debate focuses on how the decision of the majority of the magistrates has been. For this reason, the author will carry out an analysis from the argumentative approach in which he demonstrates why he finds it unjustified and arbitrary. In this line, first of all, he presents what are the problems of the sentence, identifying its argumentative fallacies. Then, he goes on to assess in detail the competence of the TC when it ruled on the matter of the interpretation of will provisions and did not consider the constitutional arguments raised by the PUCP. Secondly, the author emphasizes the need for adequate argumentation within the framework of a Constitutional State of Law. In this way, he emphasizes that any legal act, whether public or private, must be compatible with the constitutional framework. Third, he analyzes the pragmatic dimension of the legal argumentation of the aforementioned sentence, thus referring to the rhetorical resources used by the majority vote of the magistrates of the TC. In short, throughout the article the argumentative problems of the TC ruling are elucidated.